Determinación de anticuerpos anti-Fasciola hepatica en bovinos del municipio de Chiquinquirá (Colombia) - Flechas-Bernal, Juan Diego (2025)
The aim of the study was to identify antibodies against Fasciola hepatica in cattle from the municipality of Chiquinquirá, Boyacá. A descriptive cross-sectional study was carried out in which blood samples were collected from 380 female cattle. Blood serums were processed by the indirect ELISA technique using the commercial Fasciola hepatica Antibody Test Kit (IDEXX™). The general seroprevalence found was 67.37%, where animals older than 4 years (70.2%) and Jersey breed animals (84.4%) presented a higher percentage of seropositivity. The leasing of pastures and the use of cisterns as a source of drinking water showed statistical association with the presentation of Fasciola hepatica, so they were established as risk factors.